Motivation and barrier factors of environmental management systems implementation in construction - Othman, Nur Syaheera (2013)
The construction industry is one of the major sectors that contributes essential infrastructure to society and provides benefits to the country's economy. However, this thriving sector has become one of the major contributors to environmental pollution which are typically classified as air, waste, noise and water during the execution of construction activities. The promotion of environmental management and the mission of sustainable development have resulted in pressure demanding the adoption of proper methods to improve environmental performance in construction industry. The aim of the study was to investigate the level of contractor's awareness, motivation and barrier factors for the purpose of promoting ISO14001:2004-EMS in Malaysian construction industry. The level of contractor's awareness on practice towards implementation of ISO14001:2004-EMS in Malaysia's contractor companies was identified. In addition, the barriers and motivation factors were established, and furthermore the study was highlighted the effective ways on promoting ISO14001:2004-EMS in Malaysia's contractor companies. A pilot study was conducted by sending questionnaires survey to 20 selected respondents consists of EMS certified and non certified contractor companies. The final questionnaires survey was distributed to 38 EMS certified contractor companies from Grade G3 until G7 in Malaysia which have been registered with Construction Industry Development Board (CIDB). The samples were analysed by using Reliability Test, Average Index Method, Kendall's W Test and Chi- Square Test. Results show that the level of contractor's awareness are to perceived benefits and market orientation were agreed by the respondents. While, the barriers and motivation factors were mostly came from the client, employees and financial costs. The study recommended that the effective ways on promoting EMS should come from the top management, planning and documentation, education and training program, monitoring and supervision, new technologies and financial management. Finally, some recommendations were mentioned in this report.